2005
DOI: 10.1021/ef049702q
|View full text |Cite
|
Sign up to set email alerts
|

NOx Emissions of Alternative Diesel Fuels:  A Comparative Analysis of Biodiesel and FT Diesel

Abstract: This study explores the diesel injection and combustion processes in an effort to better understand the differences in NO x emissions between biodiesel, Fischer−Tropsch (FT) diesel, and their blends with a conventional diesel fuel. Emissions studies were performed with each fuel at a variety of static fuel injection timing conditions in a single-cylinder DI diesel engine with a mechanically controlled, in-line, pump-line-nozzle fuel injection system. The dynamic start of injection (SOI) timing correlated well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
114
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(125 citation statements)
references
References 16 publications
10
114
1
Order By: Relevance
“…Lapuerta et al [6] reported that lower emissions of soot, carbon monoxide (CO) and carbon dioxide (CO 2 ), but higher nitrogen oxides (NO x ), were achieved by using biodiesel in a diesel engine. Szybist et al [7] pointed out that compared to conventional diesel fuel (CDF) at high load, biodiesel blends generate 6%-9% higher NO x emissions. For gas turbine engines, Sequera et al [8] investigated the emissions of diesel and biodiesel using swirl burner gas turbine engines.…”
Section: Introductionmentioning
confidence: 99%
“…Lapuerta et al [6] reported that lower emissions of soot, carbon monoxide (CO) and carbon dioxide (CO 2 ), but higher nitrogen oxides (NO x ), were achieved by using biodiesel in a diesel engine. Szybist et al [7] pointed out that compared to conventional diesel fuel (CDF) at high load, biodiesel blends generate 6%-9% higher NO x emissions. For gas turbine engines, Sequera et al [8] investigated the emissions of diesel and biodiesel using swirl burner gas turbine engines.…”
Section: Introductionmentioning
confidence: 99%
“…Biodiesels are biodegradable and non-toxic and have lower CO and hydrocarbon emissions than petroleum-based diesel when burned [6,7]. They present, however, other technical challenges such as low cloud points and elevated NO x emissions [8].…”
Section: Introductionmentioning
confidence: 99%
“…The oil, methanol, and KOH mixture was stirred for 120 min at 60-70C and 400 rpm. The trans-esterification reaction was carried out for different ratios of oil to methanol (10,15,20,30, and 40g). The amount of catalyst had a pronounced influence on the conversion to esters.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of un-saturation of methyl esters affects the carbon to hydrogen ratio which is slightly different from conventional diesel fuel. The oxygen content is the important difference between conventional diesel fuel and biodiesel because biodiesel contains 10-12 wt% oxygen [13,14,15]. The burning efficiency of biodiesel is improved due to its high oxygen content; thus, it corresponds to lower particulate matter (PM), carbon monoxide (CO), and hydrocarbon (HC) emissions, however, and it produces higher NOx emissions [16].…”
Section: Introductionmentioning
confidence: 99%